2019
DOI: 10.1186/s12889-019-6766-5
|View full text |Cite
|
Sign up to set email alerts
|

A hard day’s night: time use in shift workers

Abstract: Background Differences in how shift workers accumulate physical activity (PA) while at work and in leisure time, on days when they are working at night, during the day, or on non-work days, are largely unexplored. The aim of this study was to improve understanding of physical activity patterns in two groups of shift workers, and to measure variations according to their shift schedules. Methods This pragmatic pilot study was conducted in two workplaces. Employees in Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Previous studies have noted that ~75% of shiftworkers have a BMI in the range of 18 to 30 kgm 2 . 63 64 Therefore, in the current study participants will be excluded if they have a BMI score of ≥30. This exclusion criteria has also been used in other laboratory based shiftworking protocols.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Previous studies have noted that ~75% of shiftworkers have a BMI in the range of 18 to 30 kgm 2 . 63 64 Therefore, in the current study participants will be excluded if they have a BMI score of ≥30. This exclusion criteria has also been used in other laboratory based shiftworking protocols.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Furthermore, while evidence exists that total physical activity does not significantly vary between shift and non-shift workers, there is mixed results on the level of engagement of moderate-to-vigorous intensity physical activity (Loprinzi 2015;Neil-Sztramko et al 2016;Roskoden et al 2017). Current evidence suggests many of these variations in physical activity intensity are attributed to occupational demands, rather than shift work directly (Kolbe-Alexander et al 2019); however, further research is required to better understand these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies that examine the physical activity and sleep of shift workers, have reported these behaviours separately (Flahr et al 2018;Kecklund and Axelsson 2016), with few studies examining both physical activity and sleep within the same study (Clark et al 2017;Kolbe-Alexander et al 2019;Varela-Mato et al 2017). It is important to examine physical activity and sleep together as they are known to co-occur, with a bi-directional relationship occurring between these behaviours (Ding et al 2015;Kline 2014;Oftedal et al 2019;Rayward et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of light bulbs, however, individuals increasingly tend to work at unusual times of the day in most industrialized countries. For example, a significant proportion (16~28%) of the population works in various shifts currently (Kervezee et al, 2018 ; Kolbe‐Alexander et al, 2019 ). Several lines of epidemiological evidence clearly indicate that those who work in shifts are more likely to develop chronic illnesses, such as obesity, type 2 diabetes, cardiometabolic consequences, and sleep disturbances (Lim et al, 2018 ; Liu et al, 2018 ; Zimmet et al, 2019 ; Zoto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%